Design and testing of an ultrasound system for targeted spraying in orchards - Jejčič, Viktor (Strojniški vestnik, 2011)
The research aims to demonstrate the basic system elements of a prototype automated orchard sprayer, which can deliver pesticide spray selectively withrespect to the characteristics of the targets. The contour of the apple tree canopy was detected by ultra sound sensors Prowave 400EP14D and appropriate electronics. Ultra sound signal was processed by a personal computer and fed in real-time to spraying nozzles which open and close in relation to the canopy structure. The current project focuses on developing the system components for spraying an individual tree. The evaluation was performed in field experiments by detecting deposits on leaves and water sensitive papers (WSP). The demonstrated concept of precise application of pesticide sprays supports a decrease in the amount of delivered spray, thereby reducing both costs and environmental pollution by plant protection products.
Keywords: air-assisted sprayer; algorithm; orchard; pršilniki; razporeditev škropiva; sadovnjaki; spray distribution; ultra sound; ultrasound; ultrazvok